Use of Digital-Conventional Method for Managing a Patient with Severely Worn Dentition: A Clinical Report - Saied Nokar; Amirreza Hendi; Yasamin Babaee Hemmati; Mehran Falahchai (Case Reports in Dentistry)
Severe forms of attrition are frequently found in patients with no or insufficient posterior occlusal support. Management of such patients using fixed or removable prostheses is a complex procedure and is still a challenge for clinicians. The present clinical report describes step by step full mouth rehabilitation of a patient with severely worn dentition using computer-aided design/computer-aided manufacturing- (CAD/CAM-) generated wax patterns, milled zirconia frameworks, and fabrication of removable partial denture (RPD) abutments using a digital-conventional method. The results were satisfactory during 18 months of follow-up.